2016
DOI: 10.1259/bjr.20151055
|View full text |Cite
|
Sign up to set email alerts
|

Ultralow dose dentomaxillofacial CT imaging and iterative reconstruction techniques: variability of Hounsfield units and contrast-to-noise ratio

Abstract: Objective: The aim of this study was to evaluate whether application of ultralow dose protocols and iterative reconstruction technology (IRT) influence quantitative Hounsfield units (HUs) and contrast-to-noise ratio (CNR) in dentomaxillofacial CT imaging. Methods: A phantom with inserts of five types of materials was scanned using protocols for (a) a clinical reference for navigated surgery (CT dose index volume 36.58 mGy), (b) low-dose sinus imaging (18.28 mGy) and (c) four ultralow dose imaging (4.14, 2.63, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 20 publications
(31 reference statements)
2
13
0
Order By: Relevance
“…The present study's finding of relative comparability of the FBP/TP2 model with the reference model is in agreement with the findings of Loubele et al [4] who reported accurate segmentation of CAD models of a skull phantom with an MDCT CTDIvol similar to that imparted by TP 2 of the present study. In the present study, MBIR produced the smoothest CAD models and lowest deviations of all the reconstruction techniques; these findings are compatible with the findings of studies which found that MBIR demonstrated more marked improvements in image quality at low doses compared with other reconstruction techniques [6,13].…”
Section: Discussionsupporting
confidence: 92%
“…The present study's finding of relative comparability of the FBP/TP2 model with the reference model is in agreement with the findings of Loubele et al [4] who reported accurate segmentation of CAD models of a skull phantom with an MDCT CTDIvol similar to that imparted by TP 2 of the present study. In the present study, MBIR produced the smoothest CAD models and lowest deviations of all the reconstruction techniques; these findings are compatible with the findings of studies which found that MBIR demonstrated more marked improvements in image quality at low doses compared with other reconstruction techniques [6,13].…”
Section: Discussionsupporting
confidence: 92%
“…24 When we compared contrast-to-noise ratios of the different reconstructions using a reference dose protocol at a CTDI vol ϭ 36.58 mGy and several ultra-low doses in a phantom study with a customized polymethyl methacrylate phantom, MBIR demonstrated the highest CNR throughout, followed by ASIR-100, ASIR-50, and FBP. 25 With MBIR, ultra-low-dose protocols at CTDI vol ϭ 4.14 and 2.63 mGy may show comparable scores for spatial resolution, which may allow a dose-reduction potential of up to 93%. 26 Compared with FBP, ASIR was not able to significantly improve spatial resolution.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, MBIR achieved a statistically significantly better CNR compared with all other reconstruction techniques, which is in line with previously published results with a phantom. 25 Hoxworth et al 27 reported a significant improvement in the evaluation of soft-tissue structures with MBIR. Compared with the reference dose protocol with FBP, CNR of both the ON and IRM showed no statistically significant difference from the following: 1) LDP-I with ASIR-50, ASIR-100, and MBIR; 2) LDP-II with ASIR-100 and MBIR; 3) LDP-III with MBIR; and 4) LDP-IV with MBIR.…”
Section: Discussionmentioning
confidence: 99%
“…When evaluating contrast noise ratio (CNR) using the SedentexCT IQ Phantom imaged with ultralow dose MSCT and IRTs, MBIR may show the highest CNR and retain the highest relative CNR, followed by ASIR 100, ASIR 50 and FBP (26). At CTDI vol of 0.53 mGy MBIR limited CNR reduction to 55% compared with a 87% reduction using FBP [ 26 ]. CNR using ASIR-100 may be better than ASIR 50 and FBP but the results seem to be not statistically significant [ 26 ].…”
Section: Contrast Resolutionmentioning
confidence: 99%